A cohort study of immune and hematopoietic functionality changes in severe aplastic anemia patients treated with immunosuppressive therapy. Issue 3 (January 2019) - Guan, Jing; Sun, Yingying; Fu, Rong; Wang, Huaquan; Ruan, Erbao; Wang, Xiaoming; Qu, Wen; Wang, Guojin; Liu, Hong; Wu, Yuhong; Song, Jia; Xing, Limin; et al.
Abstract : Abstract: To investigate if variations in immune and hematopoietic parameters correlated with immunosuppressive therapy (IST) in severe aplastic anemia (SAA) patients. A total of 115 SAA patients who received IST were included. Their immune and hematopoietic functionality changes had been evaluated at 0, 0.5, 1, 2, and 3-year(s) IST. For SAA patients with complete remission (CR), the CD4 + /CD8 + T cell ratio continued to increase after a year of IST. The T helper (Th)1/Th2 ratio continued to decrease after 6 months of IST, as did the activated CD8 + T cell percentage. The myeloid dendritic cell (mDC)/plasmacytoid dendritic cell (pDC) ratio after 3 years of IST was significantly lower compared to that of untreated patients. The mDC/pDC and Th1/Th2 ratios exhibited positive correlation. The activated CD8 + T cell percentage and the number of peripheral blood neutrophils showed inverse correlation. For SAA patients with partial remission (PR), the CD4 + T cell percentage increased at 1-year post-IST, but the later changes were not statistically significant. The other immune indexes of patients in partial remission group and nonremission (NR) group showed no obvious recovery. For all SAA patients, the percentage of T regulatory cells in CD4 + lymphocyte was higher in post-IST group compared to the pretreatment group. For SAA patients responded well to IST, increase in peripheral neutrophils and improvement in bone marrow myeloid cells were first observed followed reduction in the activated CD8 + T cell percentage, Th1/Th2 ratio, CD4 + /CD8 + T ratio, along with mDC/pDC ratio, all of which negatively correlated with the hematopoietic parameters. This demonstrates that IST prompts improvements of hematopoietic functionalities of the SAA patients by regulating their immune functionalities.